Mechanisms of diminished attention to eyes in autism - Moriuchi, Jennifer M. (Am J Psychiatry, 2016)
OBJECTIVE: Two hypotheses, gaze aversion and gaze indifference, are commonly cited to explain a diagnostic hallmark of autism: reduced attention to others' eyes. The two posit different areas of atypical brain function, different pathogenic models of disability, and different possible treatments. Existing evidence for and against each hypothesis is mixed but has heretofore focused on older children and adults. We evaluated both mechanistic hypotheses in two sets of experiments at time of initial diagnosis. METHOD: Eye-tracking data were collected in 86 two-year-olds: 26 with autism, tested at initial diagnosis; 38 matched typically-developing peers; and 22 matched developmentally-delayed peers. We measured response to direct (Experiment 1) and implicit (Experiment 2) cueing to look at the eyes. RESULTS: When directly cued to look at the eyes, two-year-olds with autism did not look away faster than their typical peers; their latency varied neither categorically, nor dimensionally, by degree of eyes cueing. Moreover, direct cueing had a stronger sustained effect on their amount of eye-looking than typical peers'. In addition, when presented with implicit social cues for eye-looking, two-year-olds with autism neither shifted their gaze away nor more subtly averted gaze to peripheral locations. CONCLUSIONS: Results falsify the gaze aversion hypothesis; instead, at time of initial diagnosis, diminished eye-looking in autism is consistent with passive insensitivity to the social signals in others' eyes.